Efficiency Policy in Hospitals with Envelopment Analysis Method - Lovita Diba Br Sinaga; Destanul Aulia; Siti Saidah Nasution (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The aim of the study is efficiency policy analysis in hospitals with data envelopment analysis method with return to scale model. The time of the research is carried out in November 2020 until completion. The sample in this study was Hospital X. The data collection technique used in this study used secondary data is obtained from the literature study method, literature exploration, and hospital annual reports. This research uses data envelopment analysis method. The results show that the average efficiency score of Hospital X for the 2017-2019 period is 0.981966, where in 2017 it is 0.998424, in 2018 it is 0.990754, and in 2019 it is 0.956721. During the research period, namely 2017-2019, it can be interpreted that Hospital X has not been technically efficient because the efficiency value is below 1 or 100 percent. It is hoped that hospital leaders will be able to implement hospital input control programs such as total hospital assets, total staff, and make efficiency in the use of operational costs so that hospital outputs such as total patients, number of health checks, and operating income can be achieved maximally. Improving quality is important so that current hospital efficiency can be achieved. Furthermore, the data envelopment analysis method can be used as one of the considerations for establishing a hospital because it is able to calculate the relative efficiency of hospitals in a particular area. Then, it can promote plenary accreditation to ensure to the public that hospital standards have been properly met.